Comparative Characteristics of International and Legal Standards in the Field of Children Rights Protection - K. V. Katerynchuk; O. L. Matsiuk (Bulletin of Kharkiv National University of Internal Affairs)
The current state of child protection through the prism of international, criminal and constitutional law has been studied. The concept of “a child” and the age limits, which are contained in the Convention on the Rights of the Child and the Family Code of Ukraine, have been analyzed. The legislation of some countries has been studied for further establishment of features and ways of counteraction to violence against children.